(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Urban road networks possesses fractal characteristics due to ordered division and structural layout of the road networks which contain inherent self-similarity and scale invariance. We investigate urban planning of road networks in the Buraydah City, Al Qassim, Saudi Arabia using techniques from fractal geometry via fractal dimension (a non-integer number which measure geometric complexity of an object) calculations. The main objective is to study the fractal structure of the road network of the Buraydah city. To accomplish this goal we provide simulation and compare various kinds of fractal dimensions including box dimension (D_box), capacity dimension (D_cap), information dimension (D_inf), correlation dimension (D_cor), and probability dimension (D_prob) for the entire road network of the Buraydah city. The study reveals that a better planning and optimization of road networks can be obtained using these fractal indicators. The computational experiments are done using QGIS software and open source fractal dimension programs to understand fractal spatial patterns in the road network.